Pemilihan Alternatif Supplier Menggunakan METODE ANALYTICAL HIERARCY PROCES (AHP) (Studi Kasus: BENGKEL SAIISOKU X KOBAYOGAS) - Irma Agustiningsih Imdam; Mikhael Pramana Putranta Sebayang; Galih Arisandy Viranski; Indra Yusuf; Dewi Auditya Marizka; Wilda Sukmawati (Journal Industrial Manufacturing, 2025)
Saiisoku X Kobayogas Workshop is a collaborative workshop between Saiisoku, a renowned motorcycle modification team, and Kobayogas, a brand recognized for its high-quality motorcycle care products. The services offered at this workshop range from routine servicing and modifications to special maintenance for motorcycle engines, including oil changes, tune-ups, and periodic condition checks. We also offer light to extreme modifications, as well as combustion chamber cleaning. In the research conducted using the Analytical Hierarchy Process (AHP) method, it can help in decision-making to choose a supplier that focuses on oil products for the Saiisoku X Kobayogas workshop. Through questionnaires given to workshop workers, data were obtained regarding various aspects of workshop services, so it is hoped that factors from various aspects can be identified to improve service quality and workshop operational efficiency. The highest criteria weight for supplier selection is the Quality criterion with a weight of 0.31, and the highest subcriteria in this criterion is consistency in product specifications with a weight of 0.440. The recommended supplier alternative to be selected based on data processing using AHP is PT Liqui Moly Indonesia, with the highest weight of 0.345.Keywords: Analytical Hierarchy Process, Supplier, Service, Efficiency